2021
DOI: 10.1016/j.ekir.2021.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease of Unknown Etiology in India: What Do We Know and Where We Need to Go

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…showed more than 70% CKDu patients in Odisha belonged to lower socioeconomic groups, and 48% were engaged in agricultural activities. 5 The prevalence of CKD was equal in the two sexes. The prevalence was ≥20% in one-third of the sampled villages, suggesting geographic clustering.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…showed more than 70% CKDu patients in Odisha belonged to lower socioeconomic groups, and 48% were engaged in agricultural activities. 5 The prevalence of CKD was equal in the two sexes. The prevalence was ≥20% in one-third of the sampled villages, suggesting geographic clustering.…”
Section: Discussionmentioning
confidence: 98%
“…Narasinghpur and Badamba blocks in the Cuttack district are regarded by the local press as hotspots. 5 Chronic kidney disease of unknown origin (CKDu) in Odisha contributes significantly to the national burden of CKD in India. Most of the affected persons are from the productive age group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In India, lead, fluoride, and chromium have been identified variably in blood or urine samples of CKDu patients [7 ▪ ,33]. Groundwater silica levels are up to eight-fold higher in endemic vs. nonendemic regions reaching 12 times higher than recommended levels [7 ▪ ,36]. It should be noted that not all studies have found correlations with nephrotoxin exposure and CKDu; thus, a definitive role in disease initiation or progression has not been proven.…”
Section: Pathogenesismentioning
confidence: 99%
“…Chronic kidney disease with unknown cause (CKDu) has recently been reported in people from poor communities in Mesoamerica [4], Sri Lanka [5,6], and India [7,8]. Initially, CKDu was suspected to be an occupational disease associated with exposures in the agricultural workplace, such as heat stress and dehydration [4], pesticide spraying [9], heavy metals and agrochemicals [10], or the use of NSAIDs [11].…”
Section: Introductionmentioning
confidence: 99%